Molecular mapping of quantitative trait loci determining resistance to septoria tritici blotch caused by Mycosphaerella graminicola in wheat - Simón, María Rosa (2004)
A set of 65 recombinant inbred lines of the ‘International Triticeae Mapping Initiative’ mapping population (‘W7984’ × ‘Opata 85’) was analysed for resistance to septoria tritici blotch at the seedling and adult plant stages. The mapping population was inoculated with two Argentinean isolates (IPO 92067 and IPO 93014). At the seedling stage, three loci were discovered on the short arms of chromosomes 1D, 2D and 6B. All three loci were detected with both isolates. At the adult plant stage, two isolate-specific QTL were found. The loci specific for isolates IPO 92067 and IPO 93014 were mapped on the long arms of chromosomes 3D and 7B, respectively.